Corn cob modified by lauric acid and ethanediol for emulsified oil adsorption - Ji, Zhen; Lin, Hai; Chen, Yue-fang; Dong, Ying-bo; Imran, Muhammad (Journal of Central South University, 2015)
Corn cob is a naturally renewable material with developed micropore and hydrophobic characteristics, which enables it to show good oil adsorption capacity. In order to improve oil adsorption capacity, corn cob was modified with lauric acid and ethanediol. The structure of raw and modified corn cob was investigated using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) method, thermogravimetric analysis (TGA) and ZeTa potential analyzer. The effects of pH level, adsorption time, adsorbent dosage, and initial oil concentration on oil absorbency of corn cob were studied. The results indicate that the modification significantly improved the lipophilicity of corn cob, making the modified corn cob with much better adsorption capacity on oil absorbency. Compared with raw corn cob, the maximum saturated adsorption capacity of modified corn cob is 16.52 mg/g at pH 5, and the increasing percentage is found to be 141%, which indicates that the modification causes a better adsorption capacity for oil removal. In addition, due to high oil adsorption capacity, affordable price and low secondary pollution, the modified corn cob could be considered promising alternative for the traditional oil adsorbent to clean up the emulsified oily water.